Analysis of Turning Performance on AISI O1 Steel Using VO+nMoS2 as Coolant. (23rd April 2022) - Sivaraman, V.; Hans, S. J. Davis; Palani, Kumaran; Atiso, Tsegaye Alemayehu; JM, Jafferson; Ross, Nimel Sworna
Abstract : AISI O1 cold work steel is a hard-to-machine material as a reason of its good temperature resistance, superficial hardness, and lesser response to wear. Hence, material removal from such hard materials is both cost- and time-consuming. Conventional cutting fluids fail to lessen the hotness at the tool-work junction. This research work explores the effects of a uniquely prepared and eco-friendly cutting fluid on the cutting performance of AISI O1 steel using tool inserts of three different materials. The prepared cutting fluid, molybdenum disulfide nanoparticle (MoS2) blended in biodegradable vegetable oil (VO) was distributed into the cutting zone with the help of the minimum quantity lubricant (MQL) technique. The integrated approach of Taguchi's average normalized S/N ratio-based RSM method was employed to model the parameters for better responses. The optimal condition predicted by the approach (the type of insert – CBN, Vc – 110.12 m/min, f – 0.08 mm/rev, and DOC – 0.20076 mm) was observed to produce noteworthy improvements in tool wear and lessen the cutting force in addition to a good surface finish. The study will offer the required guidance for tool and die industries handling AISI O1 steel and help researchers work towards sustainable machining.